(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2020)
The results indicate that Dwarf chickens were nurtured in deck cages in an open-model house of high egg mass characteristic after 112 days of egg production through selection for three generations, where the egg mass increased from 2.56 kg eggs / hen in Fo parents’ generation to 4.07 kg eggs / hen in second generation F2, when the F0, F1 and F2 generation intensity elected were estimated at 2.66%, 1.83% and 1.76% respectively, Thus the cumulative electoral difference for that characteristic in the second generation F2 was estimated at 1.49 kg eggs, Response to selection and selection effectiveness were 0.72 and 0.36 respectively, The reality heritability (h2rea.) of egg mass estimated at 0.78, and when the direct selection of egg mass recipe was found indirect selection of egg production, egg laying intensity, egg weight and clicked egg In the second generation F2, Egg production increased from 0.47 eggs per hen / day in F0 generation to 0.68 eggs / hen / day in second generation F2, egg intensity increased from 39.9% in F0 generation to 70.9% in second generation F2, egg weight from 48.1g in F0 generation to 53.3g in second generation F2, as for the clicked eggs, the amount decreased from 1.0% in F0 generation to 0.9% in F2. تشير نتائج الإنتخاب إلى أن رعاية فرخات الدجاج القزم ضمن أقفاص طابقيه في حظيرة من النموذج المفتوح قد أدى إلى إرتفاع صفة كتلة البيض بعد مضي 112 يوماً من إنتاج البيض من خلال الانتخاب لثلاثة أجيال، إذ ارتفعت كتلة البيض من 2.56 كغ بيض/دجاجة في جيل الآباء Fo إلى4.07 كغ بيض/دجاجة في الجيل الثاني F2، وذلك عند انتخاب جيل الآباء F0 والجيل الأول F1 والثاني F2 بشدة انتخاب قدرت بـ 2.66%، 1.83%، 1.76% على التوالي، وبالتالي قدر الفارق الانتخابي التراكمي لتلك الصفة في الجيل الثاني F2 بـ 1.49 كغ بيض، وبلغت الاستجابة للانتخاب وفعالية الانتخاب 0.72، 0.36 على التوالي، أما قيمة المكافئ الوراثي الحقيقي لكتلة البيض (h2rea.) فقد بلغت 0.78، وعند الانتخاب المباشر لصفة كتلة البيض وجد انتخاب غير مباشر لكل من صفة إنتاج البيض وصفة شدة وضع البيض ووزن البيضة والبيض المنقور، حيث ارتفع إنتاج البيض من 0.47 بيضة للدجاجة الواحدة/يوم في جيل الآباء F0 إلى 0.68 بيضة/دجاجة/يوم في الجيل الثاني F2، وكذلك ارتفعت شدة وضع البيض من 39.9 % في جيل الآباء F0إلى 70.9 % في الجيل الثاني F2، ووزن البيضة من 48.1غ في جيل الآباء F0إلى 53.3 غ في الجيل الثاني F2، أما بالنسبة للبيض المنقور فقد انخفضت كميتة من 1.0 % بيضة في جيل الآباء F0 الى 0.9 % بيضة في الجيل الثاني F2.